2011
DOI: 10.1111/j.1365-2133.2011.10565.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyoderma gangrenosum: a retrospective review of patient characteristics, comorbidities and therapy in 103 patients

Abstract: We present one of the largest PG case series to date. In our study, we found that biopsy of a PG lesion rarely yielded characteristic features of the disease and tissue pathology should not be used to exclude a PG diagnosis. We also found a female predominance and associations with IBD and haematological disorders. Patients with PG in this series had high rates of depression and hepatitis. Further work is needed to establish the mechanism(s) underlying these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
330
6
24

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(426 citation statements)
references
References 28 publications
31
330
6
24
Order By: Relevance
“…3,6,9 O tratamento de primeira escolha é descrito com corticoterapia sistêmica em dose imunossupressora, opção com mais evidências e sucesso terapêutico relatados, sendo também a opção preferencial em crianças. 10,12 Os resultados são rápidos, com melhora das lesões em dias a semanas, o que corrobora com a resposta satisfatória apresentada no nosso caso.…”
Section: Discussionunclassified
“…3,6,9 O tratamento de primeira escolha é descrito com corticoterapia sistêmica em dose imunossupressora, opção com mais evidências e sucesso terapêutico relatados, sendo também a opção preferencial em crianças. 10,12 Os resultados são rápidos, com melhora das lesões em dias a semanas, o que corrobora com a resposta satisfatória apresentada no nosso caso.…”
Section: Discussionunclassified
“…Treatment response of patients receiving topical treatments for pyoderma gangrenosum: a prospective cohort observational study Introduction Pyoderma gangrenosum is a rare, painful ulcerative inflammatory dermatosis that is associated with considerable morbidity 728,749 and a reported threefold increased risk of death. 729 Given that mortality in PG exceeds that of underlying comorbid disease, it may be inferred that the disease itself and/or the therapeutic interventions used for its treatment are responsible for the increased risk of death in affected patients.…”
Section: Clinical Conclusionmentioning
confidence: 99%
“…728 A 2012 retrospective cohort study in the UK has reported an adjusted incidence rate (standardised to the European standard population) of 0.63 per 100,000 person-years. 729 The development of PG was associated with a threefold increased risk of death compared with general population controls, and a 72% increased mortality over controls with IBD.…”
Section: Introductionmentioning
confidence: 99%
“…The most common presentation of PG is an inflammatory papule or pustule that progresses to a painful ulcer with a violaceous undermined border and a purulent base. More than 50% of patients with PG have an associated systemic disease, most commonly inflammatory bowel disease (14-34%), arthropathies (11-25%) and hematologic disease or hematologic malignancy (20%) [1]. Systemic lupus erythematosus (SLE) is not a commonly recognized associate of PG.…”
Section: Introductionmentioning
confidence: 99%